If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -8 = 6x + 37 Reorder the terms: -8 + 9x = 6x + 37 Reorder the terms: -8 + 9x = 37 + 6x Solving -8 + 9x = 37 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -8 + 9x + -6x = 37 + 6x + -6x Combine like terms: 9x + -6x = 3x -8 + 3x = 37 + 6x + -6x Combine like terms: 6x + -6x = 0 -8 + 3x = 37 + 0 -8 + 3x = 37 Add '8' to each side of the equation. -8 + 8 + 3x = 37 + 8 Combine like terms: -8 + 8 = 0 0 + 3x = 37 + 8 3x = 37 + 8 Combine like terms: 37 + 8 = 45 3x = 45 Divide each side by '3'. x = 15 Simplifying x = 15
| 5x-(-21)=x-(-19) | | -58=y/4 | | ((6-14)+4)*4= | | -58=-6y | | 5x-(21)=x-(-19) | | 14e^2+4x=112 | | x-(-5)=6x+10 | | 42/-6 | | a+b-a+2b= | | 1/5x+3=14 | | 4x^2-8x-77=0 | | 3x-(-1)=-16 | | 5+2y=6 | | 4x+6=24-2 | | 256*12x= | | 256*20= | | 5w-7w=4 | | 4z=1.8+3.8 | | 10/7*4 | | X-5x+3x-9x= | | 1.4(5x-.1)= | | 5/6k=7 | | -12-16*4= | | 4(z+6)-26= | | 4x/7x+28 | | 1-6x=19+3x | | 4x/27+8x | | 2(5z-1)-2(6-2z)=4 | | 3(2z-2)-3(5-3z)=3 | | 3y/4=0.6 | | 60-3(E-5)= | | -3x+8x^2+1=0 |